De AERA. Gedroomde machines en de praktijk van het rekenwerk aan het Mathematisch Centrum te Amsterdam - Alberts, Gerard; de Beer, Huub T. (Studium, 2008)
AERA. Dream machines and computing practices at the Mathematical Center  Dream machines may be just as effective as the ones materialised. Their symbolic thrust can be quite powerful. The Amsterdam ‘Mathematisch Centrum’ (Mathematical Center), founded February 11, 1946, created a Computing Department in an effort to realise its goal of serving society. When Aad van Wijngaarden was appointed as head of the Computing Department, however, he claimed space for scientific research and computer construction, next to computing as a service. Still, the computing service following the five stage style of Hartree’s numerical analysis remained a dominant chara c ter istic of the work of the Computing Department.The high level of ambition held by Aad van Wijngaarden lead to ever renewed projections of big automatic computers, symbolised by the never-built AERA. Even a machine that was actually constructed, the ARRA which followed A.D. Booth’s design of the ARC, never made it into real operation. It did serve Van Wijngaarden to bluff his way into the computer age by midsummer 1952. Not until January 1954 did the computing department have a working stored program computer, which for reasons of policy went under the same name: ARRA. After just one other machine, the ARMAC, had been produced, a separate company, Electrologica, was set up for the manufacture of computers, which produced the rather successful X1 computer.The combination of ambition and absence of a working machine lead to a high level of work on programming, way beyond the usual ideas of libraries of subroutines. Edsger W. Dijkstra in particular led the way to an emphasis on the duties of the programmer within the pattern of numerical analysis. Programs generating programs, known elsewhere as autocoding systems, were at the ‘Mathematisch Centrum’ called ‘superprograms’. Practical examples were usually called a ‘complex’, in Dutch, where in English one might say ‘system’. Historically, this is where software begins. Dekker’s matrix complex, Dijk stra’s interrupt system, Dijkstra and Zonneveld’s ALGOL compiler – which for housekeeping contained ‘the complex’ – were actual examples of such super programs. In 1960 this compiler gave the Mathematical Center a leading edge in the early development of software.